Cobalt ferrite nano magnetic material with high magnetic conductivity and low loss and preparation method thereof
By using modified propylene glycol albicanate and silicon nitride in the preparation of cobalt ferrite magnetic materials, the problems of poor material agglomeration and dispersion are solved, and the preparation of nanomagnetic materials with high magnetic permeability and low loss are achieved.
Patent Information
- Application Number
- CN202411845742.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-16
- Publication Date
- 2025-03-18
- Estimated Expiration
- 2044-12-16
AI Technical Summary
Existing cobalt ferrite magnetic materials are prone to agglomeration during the preparation process, resulting in poor dispersion of nanoparticles and affecting the material's magnetic permeability and loss performance.
Modified propylene glycol alginate is used as a binder and stabilizer, combined with auxiliary materials such as silicon nitride and barium carbonate, and through multiple sintering and grinding treatments, a cobalt ferrite nanomagnetic material with high magnetic permeability and low loss was prepared.
It effectively avoids the agglomeration problem in the preparation of cobalt ferrite, improves the uniformity and thermal stability of nanomaterials, reduces the loss of magnetic materials, and improves magnetic permeability.
Smart Images

Figure CN119650238A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of nano magnetic materials, and relates to a cobalt ferrite nano magnetic material with high magnetic permeability and low loss and a preparation method thereof. Background Art
[0002] Ferrite is a new type of non-metallic magnetic material. Compared with metal magnetic materials, ferrite has the advantages of high resistivity, high dielectric properties, and high magnetic permeability at high frequencies. The main feature of ferrite magnetic materials is that the resistivity is much greater than that of metal magnetic materials, which inhibits the generation of eddy currents and enables ferrite magnetic properties to be applied in high-frequency fields.
[0003] Cobalt ferrite is a magnetic material with certain electromagnetic, magnetic and physical properties. It is widely used in electronics, communications, energy storage and other fields. Especially among magnetic materials, cobalt ferrite has high magnetism, stability and corrosion resistance, so it plays an important role in the field of magnetic materials. In recent years, the preparation of magnetic nanomaterials has attracted more and more attention, and how to prepare magnetic nanomaterials with excellent performance has become a hot topic in current magnetic material research. Summary of the invention
[0004] The main purpose of the present invention is to provide a cobalt ferrite and a preparation method thereof. The prepared cobalt ferrite has the characteristics of high magnetic permeability and low loss.
[0005] The present invention adopts the following technical solutions to achieve the above purpose:
[0006] A cobalt ferrite nanomagnetic material with high magnetic permeability and low loss is mainly prepared from the following components:
[0007] Ferric chloride, cobalt chloride hexahydrate, manganese chloride, zinc sulfate, modified propylene glycol alginate, lithium chloride, silicon nitride, barium carbonate.
[0008] The preparation method of the magnetic material is:
[0009] S1, adding water to ferric chloride, cobalt chloride hexahydrate, manganese chloride and zinc sulfate and stirring at 40-50°C to form a mixed solution, adding tartaric acid or citric acid solution and mixing, adding ammonia water, adjusting the pH to 7.0-7.5, heating and reacting and stirring until a sol state; drying the sol into a gel, pre-calcining at a temperature of 40-50°C to obtain a pre-calcined product;
[0010] S2. Grind the pre-calcined product, add modified propylene glycol alginate, silicon nitride and barium carbonate, mix well, calcine at 800-900° C. for 2-3 hours, then cool to 500-600° C. for 1-1.5 hours, cool, grind for 1.5-2 hours, sieve to obtain cobalt ferrite nanomagnetic material.
[0011] Preferably, in the above-mentioned preparation method S1, the mass-volume ratio of ferric chloride, cobalt chloride hexahydrate, manganese chloride, zinc sulfate, water, tartaric acid solution or citric acid solution is 10 in g / g / g / g / g / mL:(3-4):(1-1.5):(0.5-0.8):(8-12):(100-120).
[0012] Preferably, in the above preparation method S1, the concentration of the tartaric acid solution is 0.8 mol / L.
[0013] Preferably, in the above preparation method S1, the concentration of the citric acid solution is 0.5 mol / L.
[0014] Preferably, in the above preparation method S1, the heating reaction temperature is 70-80°C.
[0015] Preferably, in the above preparation method S1, the temperature of the pre-calcination is 400-500°C and the time is 1-1.5h.
[0016] Preferably, in the above preparation method S1, the mass concentration of ammonia water is 20-25%.
[0017] Preferably, in the above-mentioned preparation method S2, the mass ratio of the pre-calcined product, modified propylene glycol alginate, silicon nitride and barium carbonate is 100:(20-25):(5-8):(3-3.5).
[0018] As a preferred method, the preparation method of modified propylene glycol alginate is:
[0019] Propylene glycol alginate, mannitol and tartaric acid are dissolved in water, heated to 50-60°C, stirred for 30-40 minutes, then added to molten polyethylene glycol, placed in an ice water bath and stirred until viscous, and lithium chloride is slowly added during the stirring process to obtain modified propylene glycol alginate.
[0020] Further preferably, in the preparation of the above-mentioned modified propylene glycol alginate, the mass ratio of propylene glycol alginate, mannitol, tartaric acid, water, polyethylene glycol and lithium chloride is 10:(3-3.5):(5-8):(12-15):(10-15):(12-15).
[0021] Further preferably, in the preparation of the modified propylene glycol alginate, the molecular weight of polyethylene glycol is 600-1200.
[0022] The average particle size of the cobalt ferrite nano magnetic material with high magnetic permeability and low loss prepared by the invention is 30-50nm.
[0023] The present invention has the following beneficial effects:
[0024] 1. The method for preparing the cobalt ferrite nanomagnetic material of the present invention avoids the problem of easy agglomeration in the preparation of cobalt ferrite, and effectively solves the problem of poor dispersibility of nanoparticles. The modified propylene glycol alginate added in the preparation process has the functions of a binder and a stabilizer at the same time, thereby improving the uniformity and thermal stability of the nanomaterial, thereby reducing the loss of the magnetic material and improving the magnetic permeability.
[0025] 2. In the preparation process of cobalt ferrite nanomagnetic materials, the addition of auxiliary materials such as silicon nitride and barium carbonate can improve the magnetic permeability and resistivity of the material and reduce magnetic loss and eddy current loss.
[0026] 3. During the preparation process, the materials are ground and sintered multiple times to make them evenly mixed and obtain a uniform sintered body, so that the final nanomagnetic material has the characteristics of high magnetic permeability and low loss. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] Figure 1 : SEM images of different cobalt ferrite nanomagnetic materials, wherein A is the cobalt ferrite nanomagnetic material of Example 1, B is the cobalt ferrite nanomagnetic material of Comparative Example 1, C is the cobalt ferrite nanomagnetic material of Comparative Example 2, and D is the cobalt ferrite nanomagnetic material of Comparative Example 3. DETAILED DESCRIPTION
[0028] The present invention is further explained below in conjunction with specific examples. It should be understood that these examples are only used to illustrate the present invention and are not used to limit the scope of the present invention. After reading the present invention, various equivalent modifications to the present invention by those skilled in the art all fall within the scope of protection of the claims of this application.
[0029] Example 1
[0030] Preparation of modified propylene glycol alginate:
[0031] Take 10g of polyethylene glycol 600 and heat it to a molten state; add 15g of water to 10g of propylene glycol alginate, 3.5g of mannitol, and 5g of tartaric acid, dissolve them by ultrasonication, heat to 60°C, stir for 30min, then add to the molten polyethylene glycol, place in an ice water bath and stir until it becomes viscous, and slowly add 15g of lithium chloride during the stirring process to obtain modified propylene glycol alginate.
[0032] Preparation of magnetic materials:
[0033] S1. Take 10g of ferric chloride, 4g of cobalt chloride hexahydrate, 1g of manganese chloride, and 0.8g of zinc sulfate, add 8g of water, stir for 1.5h in a water bath at 50°C to prepare a mixed solution, then add 120mL of 0.5mol / L citric acid solution and mix well, stir on a magnetic stirrer for 20min, add 20% ammonia water dropwise, adjust the pH to 7.0, increase the water bath temperature to 80°C and stir until it is in a sol state; dry the sol at about 200°C to a gel state, and pre-calculate the gel at 500°C for 1h to obtain a pre-calcined product;
[0034] S2. Grind 100 g of the pre-calcined product, add 20 g of the modified propylene glycol alginate, 8 g of silicon nitride and 3 g of barium carbonate, mix well, calcine at 900 ° C for 2 h, then cool to 500 ° C and calcine for 1.5 h, cool, grind for 2 h, pass through a standard sieve, and obtain a cobalt ferrite nanomagnetic material with an average particle size of about 50 nm.
[0035] Example 2
[0036] Preparation of modified propylene glycol alginate:
[0037] Take 15g of polyethylene glycol 1200 and heat it to a molten state; add 12g of water to 10g of propylene glycol alginate, 3g of mannitol, and 8g of tartaric acid, dissolve them by ultrasonication, heat to 50°C, stir for 40min, then add to the molten polyethylene glycol, place in an ice water bath and stir until it becomes viscous, and slowly add 12g of lithium chloride during the stirring process to obtain modified propylene glycol alginate.
[0038] Preparation of magnetic materials:
[0039] S1. Take 10g of ferric chloride, 3g of cobalt chloride hexahydrate, 1.5g of manganese chloride, and 0.5g of zinc sulfate, add 12g of water, and stir for 2h in a water bath at 40°C to prepare a mixed solution, then add 100mL of 0.8mol / L tartaric acid solution and mix well, stir on a magnetic stirrer for 15min, add 25% ammonia water dropwise, adjust the pH to 7.5, increase the water bath temperature to 70°C and stir until it is in a sol state; dry the sol at about 200°C to a gel state, and pre-calculate the gel at 400°C for 1.5h to obtain a pre-calcined product;
[0040] S2. Grind 100 g of the pre-calcined product, add 25 g of the modified propylene glycol alginate, 5 g of silicon nitride and 3.5 g of barium carbonate, mix well, calcine at 800 ° C for 3 h, then cool to 600 ° C and calcine for 1 h, cool, grind for 1.5 h, pass through a standard sieve, and obtain a cobalt ferrite nanomagnetic material with an average particle size of about 30 nm.
[0041] Example 3
[0042] Preparation of modified propylene glycol alginate:
[0043] Take 13g of polyethylene glycol 800 and heat it to a molten state; add 13g of water to 10g of propylene glycol alginate, 3.2g of mannitol, and 7g of tartaric acid, dissolve them by ultrasonication, heat to 60°C, stir for 35 minutes, then add to the molten polyethylene glycol, place in an ice water bath and stir until it becomes viscous, and slowly add 13g of lithium chloride during the stirring process to obtain modified propylene glycol alginate.
[0044] Preparation of magnetic materials:
[0045] S1. Take 10g of ferric chloride, 4g of cobalt chloride hexahydrate, 1g of manganese chloride, and 0.6g of zinc sulfate, add 10g of water, stir for 1.5h in a water bath at 50°C to prepare a mixed solution, then add 110mL of 0.5mol / L citric acid solution and mix well, stir on a magnetic stirrer for 15min, add 25% ammonia water dropwise, adjust the pH to 7.5, increase the water bath temperature to 80°C and stir until it is in a sol state; dry the sol at about 200°C to a gel state, and pre-calculate the gel at 500°C for 1h to obtain a pre-calcined product;
[0046] S2. Grind 100 g of the pre-calcined product, add 23 g of the modified propylene glycol alginate, 6 g of silicon nitride and 3.2 g of barium carbonate, mix well, calcine at 900 ° C for 2 h, then cool to 600 ° C and calcine for 1 h, cool, grind for 2 h, pass through a standard sieve, and obtain a cobalt ferrite nanomagnetic material with an average particle size of about 40 nm.
[0047] Example 4
[0048] Preparation of modified propylene glycol alginate:
[0049] Take 12g of polyethylene glycol 1000 and heat it to a molten state; add 15g of water to 10g of propylene glycol alginate, 3g of mannitol, and 6g of tartaric acid, dissolve them by ultrasonication, heat to 50°C, stir for 40min, then add to the molten polyethylene glycol, place in an ice water bath and stir until it becomes viscous, and slowly add 14g of lithium chloride during the stirring process to obtain modified propylene glycol alginate.
[0050] Preparation of magnetic materials:
[0051] S1. Take 10 g of ferric chloride, 3 g of cobalt chloride hexahydrate, 1.5 g of manganese chloride, and 0.8 g of zinc sulfate, add 10 g of water, and stir for 2 h in a water bath at 40°C to prepare a mixed solution, then add 100 mL of 0.8 mol / L tartaric acid solution and mix well, stir on a magnetic stirrer for 20 min, add 20% ammonia water dropwise, adjust the pH to 7.0, increase the water bath temperature to 80°C and stir until it is in a sol state; dry the sol at about 200°C to a gel state, and pre-calculate the gel at 400°C for 1.5 h to obtain a pre-calcined product;
[0052] S2. Grind 100 g of the pre-calcined product, add 22 g of the modified propylene glycol alginate, 7 g of silicon nitride and 3.5 g of barium carbonate, mix well, calcine at 800 ° C for 3 h, then cool to 500 ° C and calcine for 1.5 h, cool, grind for 2 h, pass through a standard sieve, and obtain a cobalt ferrite nanomagnetic material with an average particle size of about 40 nm.
[0053] Comparative Example 1
[0054] Take 10g of ferric chloride, 3g of cobalt chloride hexahydrate, 1.5g of manganese chloride, and 0.8g of zinc sulfate and dissolve them in 100g of deionized water, stir them in a water bath at 60°C for 1h, then add 120mL of 0.5mol / L citric acid solution, place it on a magnetic stirrer and stir it at a speed of 300r / min to obtain a mixed solution; add 25% ammonia water dropwise to the mixture until the pH value of the mixed solution reaches 7.5, increase the water bath temperature to 80°C and continue stirring until the mixed solution is in a sol state, and dry the obtained sol at 200°C to obtain a gel; calcine the gel at 800°C for 4h, then discharge it, grind it for 2h and pass it through a standard sieve to obtain a cobalt ferrite nanomagnetic material with an average particle size of about 50nm.
[0055] Comparative Example 2
[0056] S1. Take 10g of ferric chloride, 3g of cobalt chloride hexahydrate, 1.5g of manganese chloride, and 0.5g of zinc sulfate, add 12g of water, and stir for 1h in a water bath at 50°C to prepare a mixed solution, then add 100mL of 0.8mol / L tartaric acid solution and mix well, stir on a magnetic stirrer for 20min, add 25% ammonia water dropwise, adjust the pH to 7.5, increase the water bath temperature to 70°C and stir until it is in a sol state; dry the sol at about 200°C to a gel state, and pre-calculate the gel at 400°C for 1.5h to obtain a pre-calcined product;
[0057] S2. Grind 100 g of the pre-calcined product, add 25 g of propylene glycol alginate and 8 g of silicon nitride, mix well, calcine at 900 ° C for 2 h, then cool to 600 ° C for 1 h, cool, grind for 2 h, pass through a standard sieve, and obtain a cobalt ferrite nanomagnetic material with an average particle size of about 50 nm.
[0058] Comparative Example 3
[0059] Preparation of modified propylene glycol alginate:
[0060] Take 10g of polyethylene glycol 1000 and heat it to a molten state; add 12g of water to 10g of propylene glycol alginate, dissolve it by ultrasonication, heat it to 50-60°C, stir it for 30-40min, then add it to the molten polyethylene glycol, place it in an ice water bath and stir it until it becomes viscous, thereby obtaining modified propylene glycol alginate.
[0061] Preparation of magnetic materials:
[0062] S1. Take 10g of ferric chloride, 4g of cobalt chloride hexahydrate, 1g of manganese chloride, and 0.8g of zinc sulfate, add 12g of water, stir for 1h in a water bath at 50°C to prepare a mixed solution, then add 120mL of 0.5mol / L citric acid solution and mix well, stir on a magnetic stirrer for 15min, add 25% ammonia water dropwise, adjust the pH to 7.5, increase the water bath temperature to 80°C and stir until it is in a sol state; dry the sol at about 200°C to a gel state, and pre-calculate the gel at 500°C for 1h to obtain a pre-calcined product;
[0063] S2. Grind 100 g of the pre-calcined product, add 25 g of the above-mentioned modified propylene glycol alginate and 3 g of barium carbonate, mix well, calcine at 900° C. for 2 h, then cool to 600° C. and calcine for 1 h, cool, grind for 2 h, and pass through a standard sieve to obtain a cobalt ferrite nanomagnetic material with an average particle size of about 40 nm.
[0064] Comparative Example 4
[0065] Preparation of modified propylene glycol alginate:
[0066] Take 10g of polyethylene glycol 1000 and heat it to a molten state; add 15g of water to 10g of propylene glycol alginate, 3.5g of mannitol, and 5g of tartaric acid, dissolve them by ultrasonication, heat to 60°C, stir for 30 minutes, then add to the molten polyethylene glycol, place in an ice water bath and stir until it becomes viscous, thereby obtaining modified propylene glycol alginate.
[0067] Preparation of magnetic materials:
[0068] S1. Take 10g of ferric chloride, 3g of cobalt chloride hexahydrate, 1g of manganese chloride, and 0.8g of zinc sulfate, add 12g of water, stir for 1h in a water bath at 50°C to prepare a mixed solution, then add 120mL of 0.5mol / L citric acid solution and mix well, stir on a magnetic stirrer for 15min, add 25% ammonia water dropwise, adjust the pH to 7.0, increase the water bath temperature to 80°C and stir until it is in a sol state; dry the sol at about 200°C to a gel state, and pre-calculate the gel at 500°C for 1h to obtain a pre-calcined product;
[0069] S2. Grind 100 g of the pre-calcined product, add 25 g of the above-mentioned modified propylene glycol alginate and 3 g of barium carbonate, mix well, calcine at 900° C. for 2 h, then cool to 600° C. and calcine for 1 h, cool, grind for 2 h, and pass through a standard sieve to obtain a cobalt ferrite nanomagnetic material with an average particle size of about 40 nm.
[0070] Comparative Example 5
[0071] Preparation of modified propylene glycol alginate:
[0072] Take 12g of polyethylene glycol 1000 and heat it to a molten state; add 15g of water to 10g of propylene glycol alginate, 3g of mannitol, and 6g of tartaric acid, dissolve them by ultrasonication, heat to 50°C, stir for 40min, then add to the molten polyethylene glycol, place in an ice water bath and stir until it becomes viscous, and slowly add 14g of lithium chloride during the stirring process to obtain modified propylene glycol alginate.
[0073] Preparation of magnetic materials:
[0074] Take 100g of ferric chloride, 30g of cobalt chloride hexahydrate, 15g of manganese chloride, and 8g of zinc sulfate, add 100g of water, stir for 2h in a water bath at 40℃ to prepare a mixed solution, then add 1000mL of 0.8mol / L tartaric acid solution to mix, stir on a magnetic stirrer for 20min, add 20% ammonia water dropwise, adjust the pH to 7.0, increase the water bath temperature to 80℃ and stir until it is in a sol state; add 22g of the above-mentioned modified propylene glycol alginate, 7g of silicon nitride, and 3.5g of barium carbonate to mix, dry at about 200℃ to form a gel state, keep the gel at 800℃ for 4h, cool, grind for 2h, and pass through a standard sieve to obtain a cobalt ferrite nanomagnetic material with an average particle size of about 40nm.
[0075] Performance Testing
[0076] The performance of the nanomagnetic materials obtained in Examples 1 to 4 and Comparative Examples 1 to 4 was tested with reference to SJ20966-2006, and the results are shown in the calibration table.
[0077] Table 1 Test results
[0078]
[0079] As can be seen from the results in Table 1, the nanomagnetic materials prepared in Examples 1 to 4 of the present invention have higher magnetic permeability and lower magnetic loss, and the loss under high temperature and high frequency conditions is significantly reduced. Comparative Example 1 is a traditional method for preparing nanomagnetic materials, and the magnetic permeability of the obtained nanomagnetic materials is low and the gross loss is large; the propylene glycol alginate added in Comparative Example 2 is not modified, and the raw materials for preparation do not contain barium carbonate. Although the magnetic loss is reduced compared with Comparative Example 1, the electrical conductivity is reduced; the modification method of propylene glycol alginate in Comparative Example 3 is different, and the raw materials for preparation do not contain silicon nitride. Compared with the examples, its electrical conductivity is low and the magnetic loss is high; in Comparative Example 4, lithium chloride is not added to the modification of propylene glycol alginate, and silicon nitride is not contained in the raw materials for preparation. Its electrical conductivity is slightly higher than that of Comparative Example 3, and its magnetic loss is lower than that of Comparative Example 3; the preparation method of the magnetic material in Comparative Example 5 is different from that of the present invention, and its electrical conductivity is significantly low and the magnetic loss is high; overall, the performance of the nanomagnetic materials prepared in Comparative Examples 1 to Comparative Examples 5 is not as good as that of the nanomagnetic materials prepared in the present invention. It can be seen from the results in the attached figure that the cobalt ferrite nanomagnetic material prepared by the present invention has uniform size, while the cobalt ferrite nanomagnetic materials prepared in Comparative Examples 1-3 have grain agglomeration to varying degrees.
Claims
1. A cobalt ferrite nanomagnetic material with high magnetic permeability and low loss, characterized in that: It is prepared from the following ingredients: ferric chloride, cobalt chloride hexahydrate, manganese chloride, zinc sulfate, modified propylene glycol alginate, lithium chloride, silicon nitride, barium carbonate; The preparation method of the cobalt ferrite nanomagnetic material is: S1, adding water to ferric chloride, cobalt chloride hexahydrate, manganese chloride and zinc sulfate and stirring at 40-50°C to form a mixed solution, adding tartaric acid or citric acid solution and mixing, adding ammonia water, adjusting the pH to 7.0-7.5, heating and reacting and stirring until a sol state; drying the sol into a gel, pre-calcining at a temperature of 40-50°C to obtain a pre-calcined product; S2. Grind the pre-calcined product, add modified propylene glycol alginate, silicon nitride and barium carbonate, mix well, calcine at 800-900° C. for 2-3 hours, then cool to 500-600° C. for 1-1.5 hours, cool, grind for 1.5-2 hours, sieve to obtain cobalt ferrite nanomagnetic material.
2. The cobalt ferrite nanomagnetic material according to claim 1, characterized in that: In the preparation method S1, the mass-volume ratio of ferric chloride, cobalt chloride hexahydrate, manganese chloride, zinc sulfate, water, tartaric acid solution or citric acid solution is 10 in g / g / g / g / g / mL:(3-4):(1-1.5):(0.5-0.8):(8-12):(100-120).
3. The cobalt ferrite nanomagnetic material according to claim 1, characterized in that: In the preparation method S1, the concentration of the tartaric acid solution is 0.8 mol / L; the concentration of the citric acid solution is 0.5 mol / L.
4. The cobalt ferrite nanomagnetic material according to claim 1, characterized in that: In the preparation method S1, the heating reaction temperature is 70-80°C.
5. The cobalt ferrite nanomagnetic material according to claim 1, characterized in that: In the preparation method S1, the temperature of the pre-calcination is 400-500° C. and the time is 1-1.5 h.
6. The cobalt ferrite nanomagnetic material according to claim 1, characterized in that: In the preparation method S1, the mass concentration of ammonia water is 20-25%.
7. The cobalt ferrite nanomagnetic material according to claim 1, characterized in that: In the preparation method S2, the mass ratio of the pre-calcined product, modified propylene glycol alginate, silicon nitride and barium carbonate is 100:(20-25):(5-8):(3-3.5).
8. The cobalt ferrite nanomagnetic material according to claim 1, characterized in that: The preparation method of the modified propylene glycol alginate is as follows: Propylene glycol alginate, mannitol and tartaric acid are dissolved in water, heated to 50-60°C, stirred for 30-40 minutes, then added to molten polyethylene glycol, placed in an ice water bath and stirred until viscous, and lithium chloride is slowly added during the stirring process to obtain modified propylene glycol alginate.
9. The cobalt ferrite nanomagnetic material according to claim 8, characterized in that: In the preparation of the modified propylene glycol alginate, the mass ratio of propylene glycol alginate, mannitol, tartaric acid, water, polyethylene glycol and lithium chloride is 10:(3-3.5):(5-8):(12-15):(10-15):(12-15).
10. The cobalt ferrite nanomagnetic material according to claim 8, characterized in that: The molecular weight of the polyethylene glycol is 600-1200.
Citation Information
Patent Citations
Preparation method of cobalt ferrite nano magnetic material
CN106219610A
Mn-Zn ferrite filtering material with high magnetic permeability
CN113603473A
Particle-free iron-based conductive ink for electromagnetic function and preparation method of particle-free iron-based conductive ink
CN115820038A
Preparation method and application of nano ceramic with porous structure
CN118834061A
Ferrite magnet with salt and manufacturing method of the same
US20140070130A1